Land purchase in Ireland: a retrospect and a forecast - Lynch, Stanislaus John (Statistical and Social Inquiry Society of Ireland, 1913)
When presenting to you this evening a retrospect of the progress of Land Purchase in Ireland since 1885, it is not necessary to refer to the various causes which led up to the then existing dead-lock in the sale and transfer of Irish land, save to remind you that while the bitter agrarian and political agitation which followed upon the Fair Rent legislation of 1881 had closed the door of the Irish land market to all bidders except the occupying tenants, no adequate means had been afforded to them to become owners of their holdings upon equitable terms.
Read Friday, 29th November, 1912.
Keywords: Land purchase; Congested Districts Board; 314.15